Exploring the Challenges and Opportunities for Continuing Professional Development fo Nurses: A Qualitative Study with Senior Nurse Leaders in Nepal - Khatri, R.; van Teijlingen, E.; Marahatta, S.B.; Simkhada, P.; Mackay, S.; Simkhada, B. (Journal of Manmohan Memorial Institute of Health Sciences, 2021)
Background: Continuing professional development for nurses is internationally recognised as a key factor in improving quality of care, career progression, job satisfaction and professionalization. Meeting the global and national challenge of Universal Health Coverage will require a flexible and skilled workforce. Since nurses are the backbone of health care in Nepal, their professional development is a key contribution to this task. Objective: To explore the views of senior nurses on the need and opportunities for continuing professional development in nursing in Nepal and current barriers to its development. Methods: Purposive sampling was used to identify participants and semi-structured interviews were conducted until saturation was reached. Interviews were transcribed verbatim and analysed using thematic analysis. 19 senior nurses, female (n=17) and male (n=2) working across the sector as clinicians, teachers and managers in Nepal participated in this study. Results: Analysis revealed several themes and subthemes, including: the conceptualisation of CPD in Nepal; provision and funding; barriers – fiscal, political and geographical challenges; and future priorities which included a discussion around basic skills versus advanced practice. Conclusions: The study provides an overview of opportunities and challenges for equitable access to continuing professional development in Nepal. Our findings illuminate the need for nurse leaders to work with policy makers and nursing organisations to establish the priorities for continuing development in light of increasing demand and expectations of health services.